LGG-48. The influence of different FGFR1 alterations on pediatric low-grade glioma tumor biology and targeted therapy response. (3rd June 2022) - Morin, Eric; DiGiacomo, Jeromy; Novikov, Dana; Malinowski, Seth; Chow, Kin-Hoe; Jones, David; Alexandrescu, Sanda; Ligon, Keith; Bandopadhayay, Pratiti
Abstract: Pediatric low-grade gliomas (pLGGs) have excellent survival, however, with current standard of care, most patients suffer lifelong severe sequalae. pLGGs are almost exclusively driven by single activating mutations in the MAPK pathway. Clinical trials with small molecule inhibitors in BRAF-altered pLGGs are showing promising results in early clinical trials, and similar efforts are now underway for FGFR1-altered tumors, however the underlying biology and treatment response has not been thoroughly explored in a pre-clinical setting. To explore the genetic landscape of FGFR altered gliomas we assembled a cohort of 87 patients with FGFR1-4 altered gliomas across Dana-Farber Cancer Institute, Boston Children's Hospital and Brigham and Women's Hospital. Within this cohort we observed that pLGGs harboring FGFR1 kinase hotspot mutations (FGFR1-N546K or -K656E) frequently harbored a second alteration associated with activation of the MAPK or mTOR pathways, most commonly in the phosphatase PTPN11, NF1 or within the FGFR1 gene itself. Additionally, we observed two previously described structural variants of FGFR1, an FGFR1 internal kinase tandem duplication (FGFR-ITD) and a fusion with TACC1 (FGFR1:TACC1). The relative impact of the different FGFR1 alterations on oncogenicity, therapeutic response and resistance has not been previously explored. To address this, we have established mouse neural stem cell models overexpressing the structural variants and hot spot mutant FGFR1 alone or in combination with a second alteration. Immunoblotting revealed that the addition of a second alteration attenuated phosphorylation of ERK, AKT and S6 and influenced cell proliferation both in normal growth conditions and in absence of growth factor. Treatment with inhibitors of FGFR (Infigratinib) and MEK (Trametinib) revealed variable sensitivity both targeted therapies, suggesting that treatment of FGFR1 driven pLGG might require tailoring to the specific FGFR1 alteration.